A Diode Sensor for Air Temperature and Humidity Profile Measurements - Argete, Josefina (Science Diliman: A Journal of Pure and Applied Sciences; Vol 4 No 2 (1992), 2007)
An instrument package was developed for measuring four-level dry-bulb and wet-bulb temperature profiles. Germanium diodes (1N270) incorporated into a constant current circuit were used as sensing heads. Laboratory calibrations were referenced against a factory-calibrated thermistor with an accuracy of 0.25 deg C. The diodes showed a linear response over normal atmospheric temperature range and a sensitivity of about 1.8 mV /deg C. Field performance gave the following spread of values among the four psychrometers: 0.15 deg C for T d .05 deg C for T w and 0.15 hPa for vapor pressure. The diode psychrometers allow air temperature and humidity profile analyses over the earth-atmosphere interface wherein accuracy, flexibility in field use, and remote reading are required.